TRPA1 Ion Channel Mediates the Analgesic Effects of Acupuncture at the ST36 Acupoint in Mice Suffering from Arthritis - Yao K; Chen Z; Li Y; Dou B; Xu Z; Ma Y; Du S; Wang J; Fu J; Liu Q; Fan Z; Liu Y; et al. (Dove Medical Press, 2024)
Kaifang Yao,1,* Zhihan Chen,1,* Yanwei Li,1 Baomin Dou,1 Zhifang Xu,1- 3 Yajing Ma,1 Simin Du,1 Jiangshan Wang,1 Jiangjiang Fu,1 Qi Liu,1 Zezhi Fan,1 Yangyang Liu,1- 3 Xiaowei Lin,1- 3 Yuan Xu,1- 3 Yuxin Fang,1- 3 Shenjun Wang,1- 3 Yi Guo1,3,4 1Research Center of Experimental Acupuncture Science, Tianjin University of Traditional Chinese Medicine, Tianjin City, People's Republic of China; 2School of Acupuncture & Moxibustion and Tuina, Tianjin University of Traditional Chinese Medicine, Tianjin City, People's Republic of China; 3National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin City, People's Republic of China; 4School of Chinese Medicine, Tianjin University of Traditional Chinese Medicine, Tianjin City, People's Republic of China*These authors contributed equally to this workCorrespondence: Yi Guo; Shenjun Wang, School of Acupuncture & Moxibustion and Tuina, Tianjin University of Traditional Chinese Medicine, No. 10 Poyang Lake Road, Tuanbo New Town, Jinghai District, Tianjin, 301617, People's Republic of China, Tel +86 22-5959-6290, Email guoyi_168@163.com; shenjunwang@163.comPurpose: Acupuncture (ACU) has been demonstrated to alleviate inflammatory pain. Mechanoreceptors are present in acupuncture points. When acupuncture exerts mechanical force, these ion channels open and convert the mechanical signals into biochemical signals. TRPA1 (T ransient receptor potential ankyrin 1) is capable of sensing various physical and chemical stimuli and serves as a sensor for inflammation and pain. This protein is expressed in immune cells and contributes to local defense mechanisms during early tissue damage and inflammation. In this study, we investigated the role of TRPA1 in acupuncture analgesia.Patients and Methods: We injected complete Freund's adjuvant (CFA) into the mouse plantars to establish a hyperalgesia model. Immunohistochemistry and immunofluorescence analyses were performed to determine the effect of acupuncture on the TRPA1 expression in the Zusanli (ST36). We used TRPA1−/− mouse and pharmacological methods to antagonize TRPA1 to observe the effect on acupuncture analgesia. On this basis, collagenase was used to destroy collagen fibers at ST36 to observe the effect on TRPA1.Results: We found that the ACU group vs the CFA group, the number of TRPA1-positive mast cells, macrophages, and fibroblasts at the ST36 increased significantly. In CFA- inflammatory pain models, the TRPA1−/− ACU vs TRPA1+/+ ACU groups, the paw withdrawal latency (PWL) and paw withdrawal threshold (PWT) downregulated significantly. In the ACU + high-, ACU + medium-, ACU + low-dose HC-030031 vs ACU groups, the PWL and PWT were downregulated, and in carrageenan-induced inflammatory pain models were consistent with these results. We further found the ACU + collagenase vs ACU groups, the numbers of TRPA1-positive mast cells, macrophages, and fibroblasts at the ST36 were downregulated.Conclusion: These findings together imply that TRPA1 plays a significant role in the analgesic effects produced via acupuncture at the ST36. This provides new evidence for acupuncture treatment of painful diseases.Keywords: acupuncture, TRPA1, ST36, inflammation, immune, analgesia